(3GdeNJUQ aj Gdabgs - (3GHf YQaI , eMeO Hf eMeO Hf YQaI GdhQZej, CHh YHO Gddg,J (B803 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH ehLHGJ GdLQGM MaX GdOeGZ s
(3BNQgG (B:s
(3jfJgi HcJGH GdhUjI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B43 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B285s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdESdGejs